VHS domain - a longshoreman of vesicle lines. - Lohi, O.; Poussu, A.; Mao, Y.; Quiocho, F.; Lehto, V.P. (FEBS Letters, 2002)
The VHS (Vps-27, Hrs and STAM) domain is a 140 residue long domain present in the very NH2-terminus of at least 60 proteins. Based on their functional characteristics and on recent data on the involvement of VHS in cargo recognition in trans-Golgi, VHS domains are considered to have a general membrane targeting/cargo recognition role in vesicular trafficking. Structurally, VHS is a right-handed superhelix of eight helices with charged surface patches probably serving as sites of protein-protein recognition and docking.